The Effect of Tamarind Seeds in Fermented Liquid Feed as Pig Feed on Nutrient and Tannin Content, Lactic Acid Bacteria Population, and Fiber Fraction - Redempta Wea; Andy Yumima Ninu; Maria Milka Nurak; Bernadete Barek Koten; Yustus Serani Nong Mbeong (Faculty of Animal Science, Universitas Brawijaya, 2023)
Feed is the biggest cost in the pig livestock business, therefore it is necessary to do processing using fermentation technology by utilizing tamarind seeds in the liquid feed. This study aimed to determine the nutrient, tannins, and populations of lactic acid bacteria (LAB), and fiber fraction. This study was undertaken in May-July 2021. The study consisted of 4 treatments, namely; R0: Fermented liquid feed (FLF) of 0% tamarind seeds, R10: FLF of 10% tamarind seeds, R20: FLF of 20% tamarind seeds, and R30: FLF of 30% tamarind seeds. This study was conducted on the experimental design using a Completely Randomized Designed (CRD). The study variables were nutrient content, tannin, LAB population, and fiber fraction. The results were analyzed quantitatively using Analysis of Variance (ANOVA), and the differences between treatments were further tested by DMRT. The results showed that the percentage of using tamarind seeds in a ratio up to 30% had a very significant effect (P<0.01) on the nutrient content (dry matter, crude protein, crude fiber, nitrogen-free extract (NFE), crude fat, and ash), anti-nutrient (tannin), fiber fraction (NDF, ADF, cellulose, hemicellulose, and lignin), but did not affect (P>0.05) the population of lactic acid bacteria. In conclusion, the use of tamarind seeds up to 30% in liquid feed increases nutrient content (dry matter, crude protein, crude fiber, nitrogen-free extract (NFE), and ash), anti-nutrient (tannin), and fiber fraction content (NDF, ADF, cellulose, hemicellulose, and lignin), but was able to reduce the crude fat content and had no impact on the population of lactic acid bacteria.